2014
DOI: 10.1007/s10725-014-9935-7
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan enhances rice seedling growth via gene expression network between nucleus and chloroplast

Abstract: Chitosan, a partially deacetylated form of the natural and biodegradable biopolymer chitin, has been used as plant growth promoter in agriculture. The aim of this work was to investigate the growth promoting responses induced by chitosan at the physiological and molecular level in rice (Oryza sativa L.) seedlings. The combination of the degree of deacetylation (DD), molecular weight and concentration of chitosan had differing effects on the rice seedling growth. For the best enhancement, oligomeric chitosan wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 64 publications
7
47
0
Order By: Relevance
“…Moreover, changes in the expression level of the chloroplastic gene, ycf1, after 48 h of chitosan application in Dendrobium 'Eiskul' were detected, followed by chloroplast enlargement after 68 weeks (Limpanavech et al, 2008). A subsequent proteomics analysis for chitosan responsive proteins in rice leaves revealed that chitosan induced significant expression level changes in 352 proteins, while a co-expression network analysis revealed that many co-expressed proteins were localized in the chloroplasts (Chamnanmanoontham et al, 2015).…”
Section: Signal Transduction and Cellular Effectsmentioning
confidence: 97%
“…Moreover, changes in the expression level of the chloroplastic gene, ycf1, after 48 h of chitosan application in Dendrobium 'Eiskul' were detected, followed by chloroplast enlargement after 68 weeks (Limpanavech et al, 2008). A subsequent proteomics analysis for chitosan responsive proteins in rice leaves revealed that chitosan induced significant expression level changes in 352 proteins, while a co-expression network analysis revealed that many co-expressed proteins were localized in the chloroplasts (Chamnanmanoontham et al, 2015).…”
Section: Signal Transduction and Cellular Effectsmentioning
confidence: 97%
“…Therefore, Yin et al (2010) supposed oligochitosan as a plant vaccine that is similar with general animal vaccine [8]. Beside elicitation effect, oligochitosan also exhibits growth promotion effect for plant such as rice [9], soybean [10,11], etc. It is interesting to note that application of oligochitosan either by seed treatment [10] or through hyponex solution [11] increased seed yield of soybean from 15 to about 36%.…”
Section: Introductionmentioning
confidence: 99%
“…The products of these genes include proteins of kinase cascade, lectin-like proteins, and zinc finger protein, as well as the protein kinase AtMPK3, which is involved in the signaling cascade and performs the reception functions, signal transduction, and transcriptional regulation. A number of proteins responsible for the growth and formation of close associations of nuclear and chloroplast genomes that accumulated under the effect of chitosan (352 proteins) were detected as the result of the analysis of the rice plant proteome [1].…”
Section: Resultsmentioning
confidence: 99%
“…Among bioactive compounds, oligosaccharides, which may possess growth-regulatory activities depending on their structure, origin, and concentration, are of particular interest [1,2]. Thus, the growth of orchids (Dendrobium bigibbum var.…”
Section: Introductionmentioning
confidence: 99%